Synopsis of Lytopsenella Kieffer (Hymenoptera: Bethylidae) - Azevedo, Celso O. (Zootaxa, 2009)
Lytopsenella Kieffer, 1905, is a Bethylinae genus with two species and is hitherto restricted to southern Chile. The genus is recognized by having the marginal cell in the fore wing closed and elongate. The goal of this study is to summarize the taxonomic knowledge of the species. L. herbsti (Kieffer, 1904) and L. testaceicornis (Kieffer, 1910) are revised and illustrated. Additional taxonomic variations are added and geographic distributions are broadened. Lytopsenella is recorded from Argentina for the first time. A key for both species are provided.